ANALYSIS OF PHYSICAL FITNESS INDICATORS OF SCHOOLCHILDREN WITH SENSORY DEPRIVATION IN COMPARISON WITH RELATIVELY HEALTHY PEERS - Bukhovets, B. O.; Bondarenko, O. V.; Onyshchuk, S. O. (Rehabilitation and Recreation, 2024)
The article presents a scientific study on the analysis of physical fitness of 11-year-old schoolchildren with visual impairment in comparison with their relatively healthy peers. Repeated studies in the field of physical culture and sports in recent years have indicated a low level of physical development and physical fitness of schoolchildren with visual impairment. There is an assumption that the indicators of physical development and physical fitness of schoolchildren with visual impairment differ significantly from their relatively healthy peers, but there is a lack of modern scientific research to support this assumption. The purpose of the study is to analyze the physical fitness of schoolchildren with visual impairment in comparison with their relatively healthy peers. Research methods: theoretical (analysis of scientific and methodological literature, theoretical analysis and generalization, system analysis), pedagogical (experiment, testing), mathematical. Primary methods of mathematical processing were used to study general features of schoolchildren’s physical fitness indicators. Results of the study. Schoolchildren with visual impairment needed 0.5 seconds more to complete the speed and agility exercise compared to their relatively healthy peers. This difference is statistically significant at the level of p<0.01 and thus confirms the data that 11-year-old students with visual impairment have a significant lag in the development of speed and agility compared to their relatively healthy peers. There was also a difference in jumping rope performance in one minute, which was 7 times (p<0.01). Conclusions. Thus, the study of physical fitness indicators of 11-yearold schoolchildren with visual impairment showed that, compared to the standards of physical fitness, most of the subjects had low or satisfactory development of speed and strength, sufficient or satisfactory endurance, and satisfactory flexibility. The data obtained confirm that students with visual impairment lag behind their peers in the ability to perform work for a certain period of time without reducing productivity.